Bicuspid Valve Aortopathy: Is It Reasonable to Define a Different Surgical Cutoff Based on Different Aortic Wall Mechanical Properties Compared to Those of the Tricuspid Valve? - Pasquale Totaro; Alessandro Caimi; Giulia Formenton; Martina Musto; Martina Schembri; Simone Morganti; Stefano Pelenghi; Ferdinando Auricchio (Journal of Cardiovascular Development and Disease)
Background: In this study, we examined and compared ex vivo mechanical properties of aortic walls in patients with bicuspid (BAV) and tricuspid (TAV) aortic valve aortopathy to investigate if the anatomical peculiarities in the BAV group are related to an increased frailty of the aortic wall and, therefore, if a different surgical cutoff point for ascending aortic replacement could be reasonable in such patients. Methods: Ultimate stress tests were performed on fresh aortic wall specimens harvested during elective aortic surgery in BAV (n. 33) and TAV (n. 77) patients. Three mechanical parameters were evaluated at the failure point, under both longitudinal and circumferential forces: the peak strain (Pstr), peak stress (PS), and maximum elastic modulus (EM). The relationships between the three mechanical parameters and preoperative characteristics were evaluated, with a special focus on evaluating potential risk factors for severely impaired mechanical properties, cumulatively and comparatively (BAV vs. TAV groups). Results: The patient populations were inhomogeneous, as BAV patients reached surgical indication, according to the maximum aortic dilatation, at a younger age (58 ± 15 vs. 64 ± 13; p = 0.0294). The extent of the maximum aortic dilatation was, conversely, similar in the two groups (52 ± 4 vs. 54 ± 7; p = 0.2331), as well as the incidences of different phenotypes of aortic dilatation (with the ascending aorta phenotype being the most frequent in 81% and 66% of the BAV and TAV patients, respectively (p = 0.1134). Cumulatively, the mechanical properties of the aortic wall were influenced mainly by the orientation of the force applied, as both PS and EM were impaired under longitudinal stress. An age of >66 and a maximum dilatation of >52 mm were shown to predict severe Pstr reduction in the overall population. Comparative analysis revealed a trend of increased mechanical properties in the BAV group, regardless of the position, the force orientation, and the phenotype of the aortic dilatation. Conclusions: BAV aortopathy is not correlated with impaired mechanical properties of the aortic wall as such. Different surgical cutoff points for BAV aortopathy, therefore, seem to be unjustified. An age of >66 and a maximum aortic dilatation of >52 mm, however, seem to significantly influence the mechanical properties of the aortic wall in both groups. These findings, therefore, could suggest the need for more accurate monitoring and evaluation in such conditions.